Treatment Process for Phenolic Wastewater - Li1, Weiping; Han1, Peijiang; Shi1, Yiran; He2, Fang; Duan1, Haojie; Yang1, Peifeng (Asian Journal of Chemistry, 2014)
Hydrogen production from waste using supercritical water gasification (SCWG) is a promising approach towards cleaner fuel production and a solution for hard to treat wastes. In this paper, the catalytic gasification of phenolic wastewater was investigated in a batch reactor at 26-34 MPa, 510-550 °C, residence time of 2-5 min. The results showed that the main gas products were H2, CO, CO2 and CH4. When residence time was 5 min, temperature is 550 °C, hydrogen gasification ratio reached up to 135 %. Supercritical water gasification was proved to be an efficient technology for phenolic wastewater treatment.